Antibacterial Activity of Ethanolic Extract Siwak Stem (Salvadora persica) Against Staphylococcus aureus ATCC 25923 - Nisa’ Nur Sholikhah; Andang Arif Wibawa; Rizal Maarif Rukmana (MANILKARA: Journal of Bioscience, 2023)
Infection is caused by bacteria, one of which is Staphylococcus aureus. Infectious treatment can use Siwak as natural plants (Salvadora persica), namely Siwak plants. Salvadora persica contains Saponins, Alkaloids, Tanins, and Fenols. This study is to know the antibacterial activity of Salvadora persica stems against Staphylococcus aureus ATCC 25923 growth. Extraction method using maceration with ethanol as a solvent. The group of extract compounds was identified using various chemical reagents. Salvadora persica stem extract was made in various concentrations of 6,25%, 12,5%, 25%, and 50% by using dimethyl sulfoxide 2% (DMSO) as thinner. Chlorhexidine 0,2% was a positive control, and DMSO 2% was a negative control. Antibacterial activity test was obtained by diffusion method. Analysis data used way ANOVA test. The results ethanolic extract of the siwak stem contains a class of compounds: saponins, alkaloids, tannins, and phenols. The result showed that Salvadora persica stem extracts antibacterial activity against Staphylococcus aureus ATCC 25923. Antibacterial activity test against Staphylococcus aureus from laboratory culture showed an average of largest inhibition zone diameter on 50% concentration with 20,5 mm diameter and smallest inhibition zone at 6,25% concentration with 14 mm diameter.